Dr. William King and the Co-operator 1828-1830. - Mercer, T.W. (Manchester : Co-operative Union, 1922)
Bibliotheek E. Anseele
Dedicator: British Co-operative Union, dedicatee: Anseele, Edward (sr.)
Engels
Monografie